PEMANFAATAN IMPLEMENTASI WEBSITE APOTEK BERKAT BENGKAYANG SEBAGAI INFORMASI UNTUK MASYARAKAT KABUPATEN BENGKAYANG - Listra Firgia (EDUKASI DAN PENGABDIAN MASYARAKAT, 2021)
In the era of information technology, online information facilities are needed that aim to provide information to the public, especially Bengkayang Regency to find out every product sold by The Blessing Pharmacy in the midst of the COVID-19 situation. This community service activity aims to provide knowledge to the owner of The Blessing Pharmacy and increase insight into the website as a medium of information that is so important during the pandemic in Indonesia like this. Berkat Pharmacy is one of the largest pharmacies in Bengkayang Regency. With this website provides a high selling value, as well as increasing consumers in searching for information about The Pharmacy Blessing.